Clinical Impact of Colistin Banning in Food Animal on mcr-1-Positive Enterobacteriaceae in Patients From Beijing, China, 2009–2019: A Long-Term Longitudinal Observational Study - Zhao, Qian; Li, Yiming; Tian, Yingxin; Shen, Yueyun; Wang, Shaolin; Zhang, Ying (Frontiers in Microbiology, 2022)
The colistin resistance gene mcr-1 is emerging as a global public health concern, altering the regulation of colistin usage globally since 2017, especially in China. However, few studies have revealed the impact of policy change on the epidemiology of mcr-positive Enterobacteriaceae (MCRPE) in patients. Here, we describe a molecular epidemiological study to investigate the MCRPE in patients in China from 2009–2019. During the surveillance period, 26,080 non-duplicated Enterobacteriaceae isolates were collected in Beijing. Colistin-resistant isolates were screened by enrichment culture supplemented with colistin, and the presence of the mcr gene was determined by PCR amplification. MCRPE isolates were then analyzed by susceptibility testing, genotyping, and risk factor analysis. Of the 26,080 isolates, mcr-1 was detected in 171 (1.1%) of 15,742 Escherichia coli isolates and 7 (0.1%) of 10,338 Klebsiella pneumoniae isolates. The prevalence of mcr-1-positive E. coli (MCRPEC) showed an increasing trend from 2009 to 2016, while a decreasing trend was observed since 2017. Multi-locus sequence typing analysis showed that MCRPEC isolates had extremely diverse genetic backgrounds, and most of these isolates were non-clonal. The prevalence of MCRPE in China remained at a low level, and even showed a declining trend over the last 3 years after the banning of colistin usage as feed additive in food animal in 2017. However, colistin permission in clinical therapy could still increase the risk of MCRPE transmission and intractable infections, active surveillance and monitoring strategies of MCRPE are recommended to prolong the clinical longevity of colistin.